(untitled) (International Journal of World Civilizations and Philosophical Studies, 2025)
Traditional medicine is a system rooted in cultural practices, knowledge, and beliefs vital to the health of a Malay society. However, the Malays have varying levels of understanding of this field of medicine in curing illnesses. This study aims to determine the community's knowledge of and perspective on traditional Malay medicine. The data were gathered using a qualitative research methodology that involved robust literature review, surveys of 327 respondents, and interviews of 7 individuals. The findings of this study indicate that a mean score of 4.48 and the community suggested that herbal plants do not cause any side effects. The study's findings demonstrated that herbal treatment was perceived as effective by approximately 45.9% of the community, as evidenced by mean scores of 4.02 and 4.13. This suggests a broad adoption of various herbs and a significant endorsement for their use within the community. The study results also demonstrated that in influencing individuals to use herbs, with a mean score of 4.13. In conclusion, community understanding of the herbs’ benefits influenced the control of traditional treatments, promoting ongoing herbal practices in modern society. Most respondents have a level of community knowledge and understanding of the use of herbs in treatment.